2013
DOI: 10.3892/mco.2013.162
|View full text |Cite
|
Sign up to set email alerts
|

Extended trastuzumab therapy improves the survival of HER2-positive breast cancer patients following surgery and radiotherapy for brain metastases

Abstract: Abstract. Brain metastases usually present late during the course of breast cancer and are associated with an unfavorable prognosis. It was previously demonstrated that the status of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor type 2 (HER2) may be altered in the time window between the emergence of the primary breast tumor and the development of metastases. The aim of this study was to compare the expression of ER, PR and HER2 in pathology samples of primary br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
(58 reference statements)
1
3
0
Order By: Relevance
“…This transfer most likely occurred because the BBB in the brain tumor tissue was at least partially disrupted, which would otherwise have prevented eribulin from entering the brain. In support of this, it has been reported that eribulin reduced the size of metastatic brain tumors developed from breast cancers, suggesting that eribulin penetrated intracerebral tumors in these cases …”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This transfer most likely occurred because the BBB in the brain tumor tissue was at least partially disrupted, which would otherwise have prevented eribulin from entering the brain. In support of this, it has been reported that eribulin reduced the size of metastatic brain tumors developed from breast cancers, suggesting that eribulin penetrated intracerebral tumors in these cases …”
Section: Discussionsupporting
confidence: 53%
“…In support of this, it has been reported that eribulin reduced the size of metastatic brain tumors developed from breast cancers, suggesting that eribulin penetrated intracerebral tumors in these cases. [36][37][38] The most intriguing finding in our study was that the concentration of eribulin in the U87MG brain xenograft remained high even 24 hours after the injection (91.7 ± 35.0 nM), although its concentration in the plasma decreased below the detectable level ( Figure 4).…”
Section: Discussionmentioning
confidence: 55%
“…Trastuzumab is a humanized monoclonal antibody directed against the HER2/neu oncoprotein and has the ability to inhibit tumor growth in breast cancer patients overexpressing HER2 [26].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, HER2-positive breast cancer patients treated with palliative chemotherapy and trastuzumab were more likely to develop BrM than patients who received palliative chemotherapy alone (37.8% vs. 25.0%, p=0.028); conversely, median time to death (TTD) measured from the development of IMD was significantly longer for patients treated with palliative chemotherapy and trastuzumab, compared to those treated with palliative chemotherapy alone (14.9 vs. 4.0 months, p=0.0005), suggesting that trastuzumab might exert some biological effect, even if partial, on IMD (101). Supporting this hypothesis, studies have similarly found that trastuzumab prolongs median OS in HER2-positive breast cancer patients with IMD (102)(103)(104).…”
Section: Her2-positive Breastmentioning
confidence: 94%